The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/app.39979
|View full text |Cite
|
Sign up to set email alerts
|

Palm oil‐based organogels and microemulsions for delivery of antimicrobial drugs

Abstract: This study has been designed to develop palm oil (PO) based organogels using span 80/tween 80 mixture (OG) as a gelator system by fluid-filled structure mechanism. The results suggested formation of organogels, emulsions, and microemulsions as the proportions of PO, OG and water were varied. The emulsions were found to be thermodynamically unstable as compared to the organogels and the microemulsions. Accelerated thermal stability test suggested that all the microemulsions and the organogels of only eight comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…Patel et al [15] reported that carbohydrate polymer including internal phase emulsion gels did not exhibit coalescence for over 3 months storage, but droplet size was dependent on the phase volumes. In another study, the droplet size was shown to be dependent on the water content as well as the organogelator ratio, and as organogelator content increased the size of the globular particles increased [17].…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Patel et al [15] reported that carbohydrate polymer including internal phase emulsion gels did not exhibit coalescence for over 3 months storage, but droplet size was dependent on the phase volumes. In another study, the droplet size was shown to be dependent on the water content as well as the organogelator ratio, and as organogelator content increased the size of the globular particles increased [17].…”
Section: Resultsmentioning
confidence: 95%
“…Hence, if oleogel emulsification process will be applied in product preparation, it must be kept in mind that a separate pre-study to find out the suitable formulae providing stable emulsions is required. Span80/Tween 80 mixture was used to prepare palm oil emulsion organogels by self organization of the fluid-filled structures, but it was also indicated that only about eight formulations were stable, and the organogels were viscoelastic in nature [17]. In another approach, Patel et al [15] utilized carrageenan, xanthan gum and locust bean gum in water phase to construct high internal phase emulsion oleogels.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…To make a normal LO, unhydrogenated lecithin has been used for an organogelator [28,29], and it has been known that when synthetic lecithins containing residues of saturated fatty acids are examined, the organogel is not formed [29]. However, in this case, the polar phase forming LO is almost comprised of water [30]. As mentioned earlier, if the water used in the LO, it is difficult to stabilize the active agent which is insoluble in both water and oil.…”
Section: Preparation Of the Formulated Lomentioning
confidence: 99%